Методика досліджень у сфері мовної політики - Берегсасі Аніко; Газдаг Вільмош; Черничко Степан; Beregszászi Anikó; Gazdag Vilmos; Csernicskó István; Aniko Beregszaszi; Csernicsko Istvan (ТОВ «фірма Планер», 2020)
Резюме. В Україні мовна проблематика занадто заполітизована, а мовна політика стала одним із центральних питань державотворення і предметом численних наукових досліджень та публікацій. Дослідники мовної політики України стали активними особливо з весни 2014 року. Однак в українській філологічній науці не існує комплексного аналізу сучасних наукових методів дослідження мовної політики. У статті подано визначення поняття «мовна політика», а також підсумовано, які методологічні процедури використовують у галузі дослідження мовної політики в західній науковій літературі.

Abstract. In Ukraine, language issue is too politicized, and language policy has become one of the central issues of national construction. Language policy is the subject of numerous philological studies and publications in Ukraine. Researchers of the language policy of Ukraine have become active especially since the spring of 2014, after the Revolution of Dignity and the occupation the Crimean peninsula and aggression of Russia against Ukraine. However, in Ukrainian philological science there are no complex analyses that looked at modern research methods for studying language policy. The aim of this article is to present the recent methods and aspects of language policy research. The article gives a definition of the concept of language policy, and also summarizes what methodological procedures are used in the field of language policy research in Western scientific literature. Contrary to the optimistic definitions that language policy serves social and economic development, equality and well-being, language policy is often an effective tool for achieving unequal distribution of social goods and political assets; it is often used for that purpose. The main conclusion of this review may be that an interdisciplinary approach is obligatory in the study of language policy issues, which involves, first of all, the study of the legal framework (laws, regulations acts and orders, international agreements) relating to the regulation of language issues, and secondly, the analysis of scientific literature on the subject. In addition, census data, educational statistics, archival materials, press publications, etc. must be used. But it should be noted that a specific research method always depends on the researcher: there is no single ideal and effective method, everyone should find their own path that best suits the specific topic and purpose of the study.

Резюме. В Украине языковая проблематика слишком политизирована, а языковая политика стала одной из центральных вопросов национального строительства и предметом многочисленных научных исследований и публикаций. Исследователи языковой политики Украины стали активными особенно с весны 2014 года. Однако в украинской филологической науке не существует комплексных анализов, которые просматривали современные научные методы исследования языковой политики. В статье дается определение понятия «языковая политика», а также подведены итоги относительно методологических процедур, которые используются в области исследования языковой политики в западной научной литературе.
Research methods in the field of language policy
Методика исследований в сфере языковой политики
Keywords: мовна політика; методи дослідження; інтердисциплінарні методи; language policy; research methods; interdisciplinary methods